2006
DOI: 10.1093/jn/136.3.648
|View full text |Cite
|
Sign up to set email alerts
|

Malnourished Children Treated in Day-Hospital or Outpatient Clinics Exhibit Linear Catch-Up and Normal Body Composition

Abstract: The nutritional programming hypothesis proposes that early life malnutrition is related to an increase in body fat later in life. Brazilian boys and girls (n = 94; 4-14 y old) were studied. Malnourished children treated in a Nutrition Recovery Center, were followed up and divided into 2 groups: the Outpatient group (recovered after outpatient care, n = 28), and the Day-hospital group (recovered after day-hospital care, n = 38). They were compared with a Control group (healthy individuals without intervention, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
0
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 35 publications
3
12
0
4
Order By: Relevance
“…Among the boys, body composition was normal, even though their values were lower in comparison to those of the control group. Similar findings have also been reported with respect to bone mineral density as outlined in figure 5 [10]. Recently, we studied how glucose metabolism and insulin levels changed in children who received adequate treatment at nutritional rehabilitation centers and showed linear catch-up growth.…”
Section: What Happens After Nutritional Recovery?supporting
confidence: 82%
See 2 more Smart Citations
“…Among the boys, body composition was normal, even though their values were lower in comparison to those of the control group. Similar findings have also been reported with respect to bone mineral density as outlined in figure 5 [10]. Recently, we studied how glucose metabolism and insulin levels changed in children who received adequate treatment at nutritional rehabilitation centers and showed linear catch-up growth.…”
Section: What Happens After Nutritional Recovery?supporting
confidence: 82%
“…According to data from the municipality of São Paulo, there are over 2,000 slums with the greatest concentration in the southern zone of the city (1,107) [9]. Data on malnourished children under treatment at a center for recovery from malnutrition in São Paulo (CREN) located in that zone [10] found that over 70% of the children were born with low or insufficient weight. CREN is a center that offers treatment to children from the slums who are reported to have mild to severe malnutrition.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A study was performed with the objective of determining the body composition of previously malnourished children who adequately recovered in both height and weight after being treated at the CREN [107]. Children and adolescents, aged 4–14 y, were divided into 3 groups.…”
Section: Nutritional Recoverymentioning
confidence: 99%
“…A prevalência da desnutrição no Brasil em crianças hospitalizadas vem sendo estudada de forma isolada nos grandes hospitais, principalmente universitários, abrangendo populações com doenças variadas (3) . A obesidade, por sua vez, associa-se a várias doenças, constituindo fator de risco para hipertensão arterial, hipercolesterolemia, diabetes melito, doenças cardiovasculares, algumas formas de câncer e problemas respiratórios (4) .…”
Section: Introductionunclassified